Collaborative logical framework: An e-learning assesment tool in .LRN platform - Vega-Alvarado, Jose; Francesa-Alfaro, Agustín; Chacón-Rivas, Mario; Garita-Rodríguez, César (LACLO 2016, 2016)
In the teaching and learning process, one of the most widely used assessments under the constructivist model is to work in groups. This has many advantages, but also weaknesses such as lack of collaboration, poor organization, difficulty in assessing, poor communication, among others. This paper describes the functionality of the Collaborative Logical Framework and the redesign made by the TEC Digital Tecnol´ogico de Costa Rica (TEC) which aims to aid students and teachers to reduce the problems that can be generated working in groups, through a tool integrated in a LMS applying usability criteria on web and mobile platforms and some integrations with others applications on .LRN LMS. This was validated applying a survey to grade and postgrade students at the TEC. The results were favorable, such as the usability of the interface, in a (very low) scale of 1 to 5 (very high) average usability by the twenty seven students surveyed is 4 points.
© © 2016 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works
Keywords: e-learning; Collaborative logical framework; Software; Usability; dotLRN; Responsive; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Pedgogical work; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education